2020
DOI: 10.14302/issn.2639-3166.jar-20-3642
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bat Guano on Growth and Yield of Some Hybrid Sunflower (Helianthus Annus, L.) Cultivars in Sudan

Abstract: Today; there is an increasing demand for fertilizers due to the intensive and extensive agricultural activity to meet the ever increasing demand for food and fiber by the rapid world population expansion. This study is mainly concern with the Bat Guano which is usually collected from the Caves. This experiment was conducted at the Farm of the College of Agriculture, University of Bahri, Alkadaro, Khartoum North-Sudan during the period from July to November, 2017 with the objective to investigate the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Gerakis and Tsangarakis (1969) reported that sesame shows positive response to P and N fertilizers in the central clay plain of Sudan. Adam (1987) and Ahmed (1987) also obtained similar result at Abu Naama. However, Ahmed (1987) found no response to N and P fertilizers at El Obied Experimental Station.…”
Section: Introductionmentioning
confidence: 53%
“…Gerakis and Tsangarakis (1969) reported that sesame shows positive response to P and N fertilizers in the central clay plain of Sudan. Adam (1987) and Ahmed (1987) also obtained similar result at Abu Naama. However, Ahmed (1987) found no response to N and P fertilizers at El Obied Experimental Station.…”
Section: Introductionmentioning
confidence: 53%